Children's Math Anxiety Predicts Their Math Achievement Over and Above a Key Foundational Math Skill. Issue 5 (19th October 2020) - Pantoja, Nancy; Schaeffer, Marjorie W.; Rozek, Christopher S.; Beilock, Sian L.; Levine, Susan C.
ABSTRACT: Math anxiety negatively predicts young children's math achievement. While some researchers have suggested that math anxiety may stem from poor math ability, others have argued that math anxiety occurs at all levels of math ability. An important question is whether math anxiety predicts math achievement over and above foundational math skills. We sought to address this issue by examining whether math anxiety predicts future math achievement, controlling for number line estimation, a foundational math skill that predicts future math achievement. We found that 1st graders' math anxiety predicts their math achievement in 1st through 3rd grade, controlling for their number line estimation at the beginning of 1st grade. This finding suggests that math anxiety contributes to future math learning over and above an important foundational math skill. Additionally, we examined whether there are age differences in the relation of first-grade math anxiety to number line estimation at various scales in order to test the hypothesis that the negative effect of early math anxiety on math performance depends on task difficulty. In support of this hypothesis, early math anxiety more closely related to the 0–100 number line task in 1st graders but to the 0–1000 number line task in 3rd graders, suggesting that math anxiety most strongly relates to math skills that are at the cusp of children's understanding at particular grade levels. Together, these findings underscore the importance of fostering young children's positive emotions toward math in addition to providing them with a strong cognitive foundation for math learning.